Defence Mechanisms of Infertile Couples vs Fertile Couples - Justo, João (2010)
Defence mechanisms (DM) were investigated in infertile couples (n = 60) waiting for their first infertility consultation, making use of the Defense Mechanisms Inventory (DMI). When compared with results of fertile couples (n = 60), infertile men and women showed a significant trend to avoid the use of defence mechanisms that enable the expression of aggressive impulses as well as a tendency to overuse defence mechanisms that enable the rationalization and negation of frustrating sutations. Such data seem to indicate the presence of defensive inflexibility in couples affected by reproductive stress, while in common couples defensive flexibility is to be expected.